PENGARUH TENAGA KERJA, MODAL DAN TEKNOLOGI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Hanif Afif Naufal; Yeti Lastuti; Alifah Kusumaningrum; Dwi Ringga Edwid Dian Negara; Maulia Siti Mukharohmah (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the impact of capital, labor, and information and communication technology (ICT) on Indonesia’s long-term economic growth. Using annual time-series data from 1971 to 2024, the analysis applies an augmented Cobb-Douglas production function. Independent variables include gross fixed capital formation, labor productivity, and ICT-based capital services growth, with real GDP as the dependent variable. Initial estimates were conducted using OLS, followed by Prais-Winsten regression to correct for autocorrelation. The results show that all three variables have a positive and significant effect on economic growth. Capital contributes the most, followed by labor and technology. These findings highlight the importance of productive investment, human capital development, and digital technology adoption in achieving sustainable economic growth